THE ECONOMIC OF SCAVENGING BUSINESS IN MUBI METROPOLITAN AREA - Yahaya, Adamu (International Journal of Research -GRANTHAALAYAH, 2018)
The study examines the economics of scavenging (Baban Bola or Yan Bola), in Mubi by over increasing numbers of unemployed youths in Mubi. The data was collected through closed ended questionnaires (60) and through researcher field observation. Data obtained were qualitative and quantitatively analyzed using descriptive statistic. Result shows that materials scavenging from solid waste for recycling is dangerous done by combining through waste dumps where materials sought after handpicked. Recyclable materials are also obtained by scavengers through the process of weighing or pricing. The materials required are hence transported using a metal cart (push push) to junk collection deport and processed by sorting and grinding. They are consequently weight using the salter scale to determine their monetary worth before selling it to the junk dealers. Most materials collected by scavengers are metallic objects, glass bottles, rubbers or plastic material because demands for such materials are high by recycling industries locally. This scavenging practice is observed to by environmentally being as it helps in reducing the excess waste destined for evacuation and final disposal in addition to the job it creates. It is however, recommended that scavenging practice should be properly organized and practitioners financially empowered so that they will acquire modern tools of resources recovered from waste to bust their capacity to recover more waste which will in due course lead to low-waste society